Pharmacological inhibition of adipose tissue adipose triglyceride lipase by Atglistatin prevents catecholamine-induced myocardial damage . Issue 11 (21st June 2021) - Thiele, Arne; Luettges, Katja; Ritter, Daniel; Beyhoff, Niklas; Smeir, Elia; Grune, Jana; Steinhoff, Julia S; Schupp, Michael; Klopfleisch, Robert; Rothe, Michael; Wilck, Nicola; Bartolomaeus, Hendrik; et al.
Abstract: Aims: Heart failure (HF) is characterized by an overactivation of β-adrenergic signalling that directly contributes to impairment of myocardial function. Moreover, β-adrenergic overactivation induces adipose tissue lipolysis, which may further worsen the development of HF. Recently, we demonstrated that adipose tissue-specific deletion of adipose triglyceride lipase (ATGL) prevents pressure-mediated HF in mice. In this study, we investigated the cardioprotective effects of a new pharmacological inhibitor of ATGL, Atglistatin, predominantly targeting ATGL in adipose tissue, on catecholamine-induced cardiac damage. Methods and results: Male 129/Sv mice received repeated injections of isoproterenol (ISO, 25 mg/kg BW) to induce cardiac damage. Five days prior to ISO application, oral Atglistatin (2 mmol/kg diet) or control treatment was started. Two and twelve days after the last ISO injection cardiac function was analysed by echocardiography. The myocardial deformation was evaluated using speckle-tracking-technique. Twelve days after the last ISO injection, echocardiographic analysis revealed a markedly impaired global longitudinal strain, which was significantly improved by the application of Atglistatin. No changes in ejection fraction were observed. Further studies included histological-, WB-, and RT-qPCR-based analysis of cardiac tissue, followed by cell culture experiments and mass spectrometry-based lipidome analysis. ISO application induced subendocardial fibrosis and a profound pro-apoptotic cardiac response, as demonstrated using an apoptosis-specific gene expression-array. Atglistatin treatment led to a dramatic reduction of these pro-fibrotic and pro-apoptotic processes. We then identified a specific set of fatty acids (FAs) liberated from adipocytes under ISO stimulation (palmitic acid, palmitoleic acid, and oleic acid), which induced pro-apoptotic effects in cardiomyocytes. Atglistatin significantly blocked this adipocytic FA secretion. Conclusion: This study demonstrates cardioprotective effects of Atglistatin in a mouse model of catecholamine-induced cardiac damage/dysfunction, involving anti-apoptotic and anti-fibrotic actions. Notably, beneficial cardioprotective effects of Atglistatin are likely mediated by non-cardiac actions, supporting the concept that pharmacological targeting of adipose tissue may provide an effective way to treat cardiac dysfunction. Graphical Abstract: